Hypertriglyceridaemia-induced pancreatitis – A diagnostic and therapeutic challenge - Savitha Manavalan; Sudhinder Murali; Sudha Vidyasagar; Sabika Begum (Journal of Clinical and Scientific Research)
Hypertriglyceridaemia is a known but relatively rare cause of acute pancreatitis. It requires a high level of clinical suspicion to be diagnosed. We report a 43-year-old male with type 2 diabetes mellitus, diagnosed initially to have alcoholic pancreatitis not responding to conservative management. Serum triglycerides (TGs) were high, and this caused pancreatitis. Following lipid-lowering measures, including insulin infusion, the TG level came down and the patient improved. This case highlights the need to rule out hypertriglyceridaemia as a cause of pancreatitis, as the treatment of this entity is different.